Visitors-wildlife interactive activities towards sustainability of wildlife tourism in National Elephants Conservation Centre, Pahang. - Daud, Darishawati; Mohd, Abdullah; Hussin, Mohamed Zakaria; Mariapan, Manohar (Forest Research Institute Malaysia, 2009)
Experiencing human-wildlife interactive activities is becoming popular in wildlife tourism. The activities involve both social and environmental dimensions. Issues have cropped up to understand the human-wildlife relationships that have occurred among visitors that involving interactive activities. The relationships that have occurred in wildlife tourism need to be explored through identifying the visitors' preferences in visiting the site, the level of interaction and factors that have contributed to the relationship. A survey was conducted using questionnaire to 400 visitors in Kuala Gandah National Elephant Conservation Centre (KGNECC) in Pahang, a wildlife tourism site in Malaysia. The findings showed that respondents' highly preferred the interactive activity when compared with other activities, suggesting that there was interaction experience occurred between visitors and elephants during the activities, such as bathing, feeding and riding with the elephants. The level of interaction was identified as high when compared to observation activities such as video show, taking pictures and watching elephants. The study also showed that four factors that have contributed to human-wildlife interactive activities: the nature-based attraction (Eigenvalue: 7.89), conservation-led activities (Eigenvalue: 5.032), environmentally educative (Eigenvalue: 3.830) and human-wildlife encounter (Eigenvalue: 2.803). Further analysis using Mann-Whitney Test and Kruskal-Wallis Test found that respondents' demographic background have also influenced the generated factors of visiting KGNECC. Socio-demographic background such as origin (types of visitor), age, marital status and education level have significant relationships with factors of visiting KGNECC while gender, occupation and average monthly income have no relationship at 0.05 level of significant. The generated factors illustrate several similarities between wildlife tourism and ecotourism, that the former comprised immersing oneself and in direct contact with the environmental elements.